First Spectrum of Tungsten (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
The spectroscopic data of tungsten (W) is important for plasma science, as it is used as a diverter and in ITER. We have recorded the spectrum of tungsten on a 1.5-m Wadsworth spectrograph in the 2100--4900 í… wavelength range. The ground configuration of the neutral tungsten is 5d\({}^{4}\)6s\({}^{2}\). First excited configurations in the odd parity system are 5d\({}^{3}\)6s\({}^{2 }\)(6p + 7p + 5f + 6f) + 5d\({}^{4}\)6s6p. The 5d\({}^{4}\)6s6p configuration has already been studied. We have identified hundreds of lines in this spectrum and confirmed fifty nine levels of the 5d\({}^{4}\)6s6p configuration. Relativistic Hartree-Fock (HFR) and least squares fitted (LSF) parametric calculations were carried out to interpret the observed spectrum. We have found good agreement with the previously published data.
Keywords: Tungsten; Wadsworth spectrograph; Cowan's computer code